Antiretroviral drug-related toxicities – clinical spectrum, prevention, and management. (September 2013) - Fernandez-Montero, Jose V; Eugenia, Eugenia; Barreiro, Pablo; Labarga, Pablo; Soriano, Vicente
Abstract : Introduction: The number of HIV patients receiving antiretroviral therapy is increasing worldwide, as new infections continue to occur and access to drugs is scaling up in most developing regions. Due to the efficacious nature of combination antiretroviral therapy in most drug-adherent patients, the concerns on the safety profile of these lifelong medicines have attracted great attention. Areas covered: Side effects of antiretroviral agents can be clinically symptomatic or manifest only as laboratory abnormalities. Drug-related toxicities can be grouped by antiretroviral drug class or damage of distinct body organs/systems. By mechanism, antiretroviral-associated adverse events generally result from hypersensitivity reactions, direct cytopathic effect, or idiosyncratic phenomena. Expert opinion: A good knowledge of the toxicity profile of antiretroviral agents is warranted for HIV care providers in order to prevent and avoid unwanted complications.